Emotions and Career Choices of High School Students - Prévost, Vicky; Savard, Réginald; Goyer, Liette (Canadian Journal of Counselling and Psychotherapy, 2024)
Although emotions are omnipresent in people’s lives and are involved in decision-making, the current state of knowledge is insufficient when it comes to emotions and career choices in high school. Yet, teenagers are required, when experiencing a life stage of intense emotion, to make a career choice that will influence their future. This study indicates the emotions felt by students during their final year of high school and the presence of relationships between some variables. Quantitative data collected by an online survey of 674 students reveals a strong presence of emotions felt in their career choices. The data also indicates that students’ receptiveness toward and understanding of their emotions is related to the degree of certainty and the experience of career choice. This article provides avenues for intervention in career counselling for guidance counsellors.